The short-term effectiveness of balance taping on acute nonspecific low-back pain: A case report. Issue 51 (December 2017) - Lee, Jung-Hoon
Abstract: Rationale: Low back pain has a significant socioeconomic impact. Repetitive lifting, with combined twisting and flexion motions of the lumbar spine, increases the risk for low-back pain and injury to the supporting tissues. Patient concerns: A 60-year-old male who presented with acute low-back pain, with a pain intensity of 6/10 on the visual analog scale (VAS) and an Oswestry disability index (ODI) score of 70%. The range of motion (ROM) of the lumbar spine on initial examination, relative to the normal peak ROM, was as follows: extension, 12°/30°; flexion, 15°/80°; left rotation, 15°/45°; and right rotation, 25°/45°. Diagnoses: He was diagnosed as acute nonspecific low-back pain sustained with repetitive lifting, combining motions of flexion and twisting. Interventions: The balance taping was applied for 16 h/day, on average, for 3 consecutive days was used as the primary treatment to manage the patient's low-back pain. Outcomes: The application of balance taping increased the range of motion of the lumbar spine as follows: flexion, from 15° to 77°; extension, from 12° to 27°; right rotation, from 25° to 45°; and left rotation, from 15° to 45°. The ODI score decreased from 70% to 0%, and the VAS score from 6/10 to 0. Lessons: We propose that balance taping using kinesiology tape could serve as a complementary approach to other treatments for the treatment of acute nonspecific low-back pain.